Non-pharmacological methods for pain relief during labor: Experience report and an integrative review (Research, Society and Development, 2021)
Introduction: Pain during labor can be modulated by non-pharmacological agents, however, its mechanisms are not fully elucidated. The purposes of this study were to identify scientifical productions in the literature regarding non-pharmacological methods for pain relief during labor in association with an experience report. Methods: It is an integrative review conducted through access to VHL, Embase and MEDLINE databases using the keywords, respectively, from DECS, Emtree e MESH in 2021 february. Full articles in English, Portuguese or Spanish from original researches were included in the time cut from 2015 to 2020, and which presented non-pharmacological methods for pain relief during labor. In addition, this work aimed to describe an undergraduate experience in the Physical Therapy course in a public maternity of a city in the countryside of Rio Grande do Sul (Brazil). Results: Twenty articles highlighting the issue were found which applied massage, walking, vertical positions, breathing exercise technique, pelvic exercise, musicotherapy, birth ball, warm aspersion or immersion, kinesio taping and tanscutaneous electrical stimulation (TENS). Extension program involved 13 parturients who were assisted by, in an isolated and combined manner, with therapeutic methods; in addition, we encouraged freedom of movement and vocalization. Conclusion: These methods bring to the conclusion that may be comfort measures in the assistance according to the integrative review. Further studies are required in order to qualify and strengthen physiotherapeutic approach in labor.